LEARNING ORGANIZATION: STRATEGY DEALING WITH THE COMPLEXITY CHANGES IN THE STATE ISLAMIC HIGHER EDUCATION (IHE) Case Study at IAIN Tulungagung and STAIN Kediri, East Java-Indonesia - Agus Zaenul Fitri (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2015)
Changing status, both the changing institutional status of a college into the institute and the institute into a university, happening in the state Islamic Higher Education (PTAIN) in Indonesia now is being a new hope for the education quality improvement. Its implication requires the changes both in terms of mindset, paradigm, human resources, infrastructure and facilities, costs, as well as culture which needs a relatively long time if nothing is done to speed up the organization learning process. One of the ways how to speed up the organization learning process is through what so-called Learning Organization (LO). LO is characterized by a movement performed by all individuals in the organization to develop their personal capacity in order to improve their best performance. However, the efforts of developing the organization are often not supported by a manager who is able to translate the vision of the leadership. That is why, the idea of idealism is still becoming a lip service. It means that it has not become a structured and systematic action which actually can accelerate the development for the better organization if it is ultimately done. The biggest problem in conducting the LO is in term of mindset change and quality culture. The strength of the organization lies in the capability of the organization to learn fast. This research found out that the organization can learn because of the encouragement of the leaders and individual that are very critical to determine its success.Keywords: Learning Organization, Change, Leadership, Culture.